2007
DOI: 10.1002/hbm.20412
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐based morphometry of the anterior cingulate cortex in first episode schizophrenia

Abstract: The anterior cingulate cortex (ACC) appears to be critically involved in the pathophysiology of schizophrenia, but past attempts at characterizing pathological changes in the region using magnetic resonance imaging have been restricted by a limited appreciation of its functional and anatomical diversity and a reliance on relatively coarse metrics (e.g., volume) to index anatomical change. In this study, we applied a novel, surface-based protocol to T1-weighted scans acquired from 40 first episode schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 100 publications
9
61
0
4
Order By: Relevance
“…This measure allows an exact in vivo quantification of cortical folding at about 300,000 points of the whole cortical mantle. Mean curvature has already been used in several studies in psychiatric diseases (e.g., schizophrenia, Williams syndrome) [31,[33][34][35] (for a detailed methodical description, see [36].…”
Section: Mri Scan Processing and Calculation Of Cortical Foldingmentioning
confidence: 99%
“…This measure allows an exact in vivo quantification of cortical folding at about 300,000 points of the whole cortical mantle. Mean curvature has already been used in several studies in psychiatric diseases (e.g., schizophrenia, Williams syndrome) [31,[33][34][35] (for a detailed methodical description, see [36].…”
Section: Mri Scan Processing and Calculation Of Cortical Foldingmentioning
confidence: 99%
“…Since VBM is prone to smoothing across neighbouring gyri [20][21][22], we sought to investigateindependently of smoothing -whether LGI changes match the topography of structural alterations previously reported in voxel-based morphometry (VBM) studies on NSS in schizophrenia. Specifically, we hypothesized that patients with higher NSS will exhibit significant LGI changes in cortical regions essential for regulating motor activity such as the precentral and paracentral gyrus, the postcentral lobe, and the prefrontal cortex, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent VBM studies found schizophrenia patients with high NSS scores to be characterized by morphological abnormalities of cortical grey matter volume (GMV) in the postcentral gyrus, precentral cortex, supramarginal gyrus, inferior parietal lobule, and inferior frontal gyrus, respectively[7,48,49]. However, VBM attempts to minimize sulcal pattern variations when normalizing MRI images into standard space and that difference in image alignment may lead to inconsistent results in morphologically variable cortical regions[21,22,61]. VBM-derived GMV is a composite measure depending on the variability of cortical parameters such as cortical thickness, area and gyrification.…”
mentioning
confidence: 99%
“…Surface-based MRI studies showed that cortical thickness is reduced in chronic (Kuperberg et al, 2003;Nesvag et al, 2008;Schultz et al, 2010a) and first-episode schizophrenia (Narr et al, 2005;Schultz et al, 2010b) in mainly the frontotemporal, but also parietal regions. ROI analyses showed cortical thinning in key regions of the medial surface, including the anterior cingulum (Fornito et al, 2008) and the entorhinal cortex (Schultz et al, 2010c). As cortical thickness is assumed to reflect neurodevelopmental mechanisms (Hilgetag and Barbas, 2006), cortical thickness might be a suitable parameter for the investigation of a potential association of genetic variants and brain morphology.…”
Section: Introductionmentioning
confidence: 99%